Pediatric case report on magnetic resonance imaging/transrectal ultrasound-fusion biopsy of rhabdomyosarcoma of the bladder/prostate: a new tool to reduce therapy-associated morbidity? - Kuru, Timur Hasan; Röthke, Matthias C.; Nyarangi-Dix, Joanne; Okouoyo, Stella; Stockklausner, Clemens; Schenk, Jens-Peter; Debus, Jürgen; Roth, Wilfried; Teber, Dogu; Pahernik, Sascha; Schlemmer, Heinz-Peter; Hohenfellner, Markus; et al. (Urology, 2013)
Rhabdomyosarcomas are the most common soft tissue sarcomas in children. Here we present management of an 18-month-old boy with metastatic rhabdomyosarcoma of the bladder/prostate. After radiochemotherapy, high-spatial-resolution 3-Tesla multiparametric magnetic resonance imaging (MRI) showed regressive systemic disease but a residual mass at the right seminal vesicle. For histologic re-evaluation, 3-dimensional-controlled stereotactic MRI/transrectal ultrasound (TRUS)-fusion biopsy specimens were taken. Because histologic analysis showed nonvital tissue, a decision could be made against adjuvant radical cystoprostatectomy. Advanced 3-Tesla imaging and MRI/TRUS-fusion biopsies in children are feasible and represent an effective tool to examine suspicious pelvic lesions. Depending on histology, this can lead to a significant reduction of therapy-associated morbidity.
Gesehen am 12.07.2021